2017
DOI: 10.18632/oncotarget.15207
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and survival outcome of breast cancer in a nationwide study

Abstract: Breast cancer is among the most prevalent cancers in Taiwan. The National Health Insurance database was used to identify patients with breast cancer and estimate the yearly prevalence and incidence of breast cancer between 1997 and 2013. Joinpoint regression analysis was used for the annual percentage change of incidence, prevalence, and survival outcome. Among 12,181,919 female beneficiaries in 2013, the prevalence was 834.37 per 100,000 persons (95% confidence interval, 829.28–839.45) and the incidence was 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 35 publications
2
45
1
3
Order By: Relevance
“…In 2013, the estimated incidence of BC in Taiwan was 93 per 100,000 person-years [3]. Our study found that the incidence of BC among women having antipsychotics was 30%-70% higher than that reported in the general population.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In 2013, the estimated incidence of BC in Taiwan was 93 per 100,000 person-years [3]. Our study found that the incidence of BC among women having antipsychotics was 30%-70% higher than that reported in the general population.…”
Section: Discussioncontrasting
confidence: 46%
“…Age is a well-recognized risk factor for BC [22], and we observed differences in the age Research Frank Huang-Chih Chou distribution of women included in each of the three groups, with almost half of all women in the typical group (49.20%) aged between 40-69 years, versus 37.79% and 36.69% in the risperidone and other atypical groups. In Taiwan, BC incidence rates increase markedly after 49 years of age [3], and the disparity in age distribution between groups may have caused the difference in BC incidence rates in the crude analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing nationwide health insurance claims data, Liu et al reported that the incidence of breast cancer almost doubled from 52.34 per 100 000 person‐years in 1997 to 93.00 per 100 000 person‐years in 2013. Even though the overall 5‐year mortality rate was similar between 1997 and 2008 (4.5% vs 4.5%), the mortality rate of patients with breast cancer and comorbidities in Taiwan improved (39.1% vs 21.1%) . Long‐term quality of life is, therefore, an important issue in patients with breast cancer, particularly older patients or those with comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the overall 5-year mortality rate was similar between 1997 and 2008 (4.5% vs 4.5%), the mortality rate of patients with breast cancer and comorbidities in Taiwan improved (39.1% vs 21.1%). 2 Long-term quality of life is, therefore, an important issue in patients with breast cancer, particularly older patients or those with comorbidities.…”
Section: Introductionmentioning
confidence: 99%